Pengaruh Konsentrasi Polivinil Alkohol terhadap Sifat Fisik dan Kimia Sediaan Peel-off Mask Ekstrak Etanol Kayu Secang (Caesalpinia sappan L.) - Dian Eka Ermawati; Lutfan Prastyo Adi (Journal of Applied Agriculture, Health, and Technology, 2023)
Free radicals can be prevented with antioxidant agents. Secang wood contains anthocyanin and flavonoid which have the potential as an antioxidant. Peel-off Mask is a gel cosmetic preparation that is practical because it does not require water. Secang wood extract can be developed as an active ingredient in peel-off mask preparations for the treatment of skin problems caused by exposure to free radicals. The formation of the plastic film on the peel-off mask depends on the concentration of polyvinyl alcohol (PVA) as a polymer. The purpose of this study was to examine the effect of PVA concentration on the physicaochemical properties of the peel-off mask preparation of sappan wood ethanolic extract. This research is a laboratory experimental study, the sappan wood was macerated with 96% ethanol solvent for three days with a ratio of 1:5. Peel-off mask formula with variations in PVA concentration of 12%, 13%, and 14%. Evaluation of the physical properties of the preparations carried out were organoleptic test, homogeneity test, dry time test, viscosity test, dispersion test and evaluation of chemical properties, namely pH test for four weeks. The data obtained were analyzed theoretically and statistically using the One-Way ANOVA method with SPSS 21. The results showed that variations in concentration had a significant effect on the consistency, viscosity, dispersion, and drying time of the peel-off mask of sappan wood ethanolic extract. The concentration of PVA that had the best evaluation was PVA 14% with a thick consistency; drying time 19,77±1,86 minutes; pH 6,33±0,21; viscosity 80,0±12,06 dPa.s; and spreadibility 5,76±0,41cm.